ANALISIS PENGEMBANGAN KURIKULUM 2013 PADA PEMBELAJARAN BAHASA ARAB DI SMP PLUS NURUL HIKMAH PAMEKASAN PERSPEKTIF TEORI GEORGE A. BEAUCHAMP - Fini Adila Kurnia; Mamluatu Solihah; Fathi Hidayah (INCARE, International Journal of Educational Resources, 2022)
This study aims to analyze the development of the Arabic curriculum with the perspective of George A. Beauchamp's theory. This research was conducted at SMP Plus Nurul Hikmah Pamekasan. The research design used is qualitative research with a literature study approach. The data are obtained by observation techniques, interviews and document studies. The primary data for this study is the Arabic curriculum used at SMP Plus Nurul Hikmah Pamekasan. The result of this study is the application of the 2013 curriculum, especially in Arabic language learning at SMP Plus Nurul Hikmah Pamekasan, it can be said that there is a compatibility with the Beaucampp curriculum model, these things can be clearly described as follows: establishing or determining an arena (scope) of the region, establishing Personnel, organizing and curriculum development procedures, implementing curriculum, organizing curriculum evaluation.